2015
DOI: 10.18203/2320-1770.ijrcog20151307
|View full text |Cite
|
Sign up to set email alerts
|

WHO 75 gram OGTT-A single step procedure for screening and diagnosis of gestational diabetes mellitus

Abstract: Background: Indian women have an eleven fold increased risk of developing glucose intolerance during pregnancy compared to Caucasian women .Universal screening for GDM is essential in India. This study was undertaken to find out a single step procedure which serves both as a screening and a diagnostic tool. Methods: This study was carried out in a tertiary care teaching institute in Karnataka. 839 pregnant women with gestational age between 24-28 weeks were subjected to 50 gram OGCT and venous blood was drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Dash et al, (2021) compared random 75 g oral glucose tolerance test (OGTT) by DIPSI criteria with fasting 75 g OGTT by IADPSG criteria in diagnosing GDM and compare outcomes of patients diagnosed with these two criteria. The study include 24 -42 weeks gestational age of pregnant women, as this is a vulnerable period where the chances of detecting the GDM cases were more when compared to 24 -28 weeks of gestational period [20,21]. The study finding showed that incidence of GDM was 12% with DIPSI and 11.3% with IADPSG criteria.…”
Section: Advantage Of Dipsi Criteria Over Other Methodsmentioning
confidence: 99%
“…Dash et al, (2021) compared random 75 g oral glucose tolerance test (OGTT) by DIPSI criteria with fasting 75 g OGTT by IADPSG criteria in diagnosing GDM and compare outcomes of patients diagnosed with these two criteria. The study include 24 -42 weeks gestational age of pregnant women, as this is a vulnerable period where the chances of detecting the GDM cases were more when compared to 24 -28 weeks of gestational period [20,21]. The study finding showed that incidence of GDM was 12% with DIPSI and 11.3% with IADPSG criteria.…”
Section: Advantage Of Dipsi Criteria Over Other Methodsmentioning
confidence: 99%